The Effect of Service Quality and Corporate Image on Student Satisfaction and Loyalty in TVET Higher Learning Institutes (HLIS) - Hassan, Sallaudin; Shamsudin, Mohd Farid; Mustapha, Ishamuddin (Journal of Technical Education and Training, 2019)
The 11th Malaysia Plan has emphasised that TVET HLIs is expected to increase the number of enrolment, improve quantity and quality of graduate to meet industry demand. This is not an easy task.  In a competitive higher learning sector, previous researches revealed that TVET institutes is facing challenges such as service quality and image issue which could have effect the level of student satisfaction and loyalty. Thus, the main objective of this research is to measure the linkages of service quality, corporate image, student satisfaction and loyalty in one framework for TVET HLIs. Stimulus- Organism- Response (SOR) model is adapted to conceptualise the relationship between the constructs. Six hypotheses have been developed. The scope of study is focus on student from TVET HLIs under higher education institutes of Council of Trust for the People (MARA). Since this study adapted quantitative method, a set of questionnaire was used for data collection. 398 data were collected and analysed using SPSS and PLS-SEM. The measurement model indicated that the measurement items are reliable and valid. The structural model indicates that there is a direct and significance effect between service quality, corporate image, student satisfaction and student loyalty. Thus, all hypotheses are supported. This research suggested that future research to investigate the mediating effect in the research framework and the scope of study to be extended to other TVET HLIs.